Predictors of 5-year mortality in patients with congestive heart failure and implanted devices for cardiac resynchronization therapy. (25th November 2020) - Soldatova, A; Kuznetsov, V.A; Dyachkov, S.M
Abstract: : Cardiac resynchronization therapy (CRT) has a wide range of therapeutic benefits including reduction in hospitalizations and death in appropriately selected patients, while the appropriate selection remains the cornerstone of CRT. Apart from the current selection criteria, many additional factors may play an incremental role affecting cardiac prognosis and CRT efficacy. Aim: To examine the ability of a multiparametric score to predict 5-year mortality in patients with congestive heart failure (HF) treated with CRT. Methods: The study enrolled 218 HF patients (83% men, 17% women; mean age of 58.7±10.7 years) with left ventricular ejection fraction (LVEF) ≤35%, NYHA class II-IV. 130 patients (59.6%) had ischemic etiology of HF (84 with prior myocardial infarction), 88 patients (31.4%) – non-ischemic cardiomyopathy. 57.3% of patients had left bundle branch block (LBBB), mean QRS width was 150.5±38.4 ms. Results: The mean follow-up period was 38.8±20.9 months. The 5-year survival was 69.3%. Points were calculated from 11 parameters identified as factors associated with all-cause mortality in multivariate analysis: gender (female – 0, male – 1); etiology of HF (non-ischemic – 0, ischemic – 1); history of myocardial infarction (no – 0, yes – 1); NYHA (II or III – 0, IV – 1); QRS (≥150 ms or ≤120 ms + 3 parameters of mechanical dyssynchrony – 0, 120–149 ms – 1); rhythm (sinus or radiofrequency ablation of atrial fibrillation (AF) – 0, AF – 1); LBBB (LBBB – 0, non-LBBB – 1); LVEF (>30% – 0, ≤30% – 1); frailty (not frail – 0, frail – 1); PR interval (<200 ms – 0; ≥200 ms – 1); NT-proBNP (median value) (<1788 pg/ml – 0, ≥1788 pg/ml – 1). To calculate the score, the sum of points was divided by the number of parameters. If less than 3 items were missing the denominator adjusted accordingly. The 5-year survival rate for patients with highest tertile score (>0.44; n=43) was 43.1%, for middle tertile (0.44≤ score ≥0.22; n=124) – 73.4% and 88.4% for lowest tertile (<0.22; n=51) (Log rank p<0.001). Conclusions: Multiparametric score can be used to predict 5-year mortality in patients with CRT. Funding Acknowledgement: Type of funding source: None